2020
DOI: 10.3390/ijerph17218284
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Physical Activity, Anxiety, Resilience and Engagement on the Optimism of Older Adults

Abstract: The purpose of this study was to learn how physical activity, anxiety, resilience and engagement can influence optimism in older adults. An observational, quantitative, descriptive and transversal design was used with non-probabilistic sampling. A descriptive statistical analysis of the sample, Cronbach’s alpha test of internal consistency and linear correlation using Pearson’s correlation coefficient (r) were performed. In addition, a t-Student test, analysis of variance (ANOVA), Kolmogorov–Smirnov test of no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 58 publications
0
16
0
Order By: Relevance
“…Optimism has repeatedly been associated with resilience (Chopik et al, 2021; Scheier & Carver, 2018) and is a well-known characteristic of individuals who are resilient. Optimism also has been found to be beneficial for both physical and psychological health and has played a pivotal role in building resilience in people who experienced traumatic situations (Martínez-Moreno et al, 2020). In this sense, it is believed that older adults who have high optimism may be more likely to be resilient.…”
Section: Discussionmentioning
confidence: 99%
“…Optimism has repeatedly been associated with resilience (Chopik et al, 2021; Scheier & Carver, 2018) and is a well-known characteristic of individuals who are resilient. Optimism also has been found to be beneficial for both physical and psychological health and has played a pivotal role in building resilience in people who experienced traumatic situations (Martínez-Moreno et al, 2020). In this sense, it is believed that older adults who have high optimism may be more likely to be resilient.…”
Section: Discussionmentioning
confidence: 99%
“…Kukihara et al (2018) found that resilience fully mediated the relationship between physical activity and depression in Japanese older adults. Similarly, a Brazilian study (Wermelinger Ávila et al, 2017) and a Spanish study found that physically active individuals have greater levels of resilience and better mental health (Martinez-Moreno et al, 2020).…”
Section: Introductionmentioning
confidence: 96%
“…Nevertheless, most of the evidence relies on cross-sectional designs, which makes it difficult to interpret cause-effect relationships (Kukihara et al, 2018; Martinez-Moreno et al, 2020; Wermelinger Ávila et al, 2018). In a 2020 article on the psychological concepts of resilience in old age and recommendations for future research, the authors stress the importance of prospective longitudinal studies (Infurna, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…It has become imperative thought to define the eminence of the aged, a multifaceted idea, and the key emphasis is how to magnify purposeful years in an advanced life period (Annele et al, 2019). As a multidimensional cycle of life, it involves resiliency with positive coping to escape from age-related morbidity and frailty, the preservation of physiological and perceptive ability, and constant social and engagement to dynamic events (Martínez-Moreno et al, 2020;Moore et al, 2015). In the process of aging, health-related events occur that compromise activities or even independence emergent evidence have demonstrated concerns among older persons in achieving successful aging, especially during the COVID-19 pandemic crisis, which has resulted in difficulty achieving physical independence, satisfaction, and other related societal appreciation.…”
Section: Introductionmentioning
confidence: 99%
“…The idea of adapting and resilience play a role in achieving a positive outcome that can help promote quality of life in this population (Sun et al, 2020;Laird et al, 2019;Xu et al, 2019;Huisman et al, 2017;Jeste et al, 2013;van Kessel, 2013). Likewise, maintaining psychological, physiological, emotional, and social health support are possible domains to attain agingrelated resiliency in older adults that can influence their optimistic outlook toward aging (Carandang et al, 2020;Knepple Carney et al, 2021;Martínez-Moreno et al, 2020;Jeste et al, 2019;Kim et al, 2018;Laird et al, 2019;Musich et al, 2019;Legdeur et al, 2018;Wister et al, 2018;Hadley et al, 2017;MacLeod et al, 2016;Fredriksen-Goldsen et al, 2015).…”
Section: Introductionmentioning
confidence: 99%